Penerapan Hukum Pidana terhadap Pelaku Tindak Pidana Perjudian dalam Lomba Pacuan Kuda yang Melibatkan Anak: Studi di Kabupaten Sumba Timur - Richard Hina Wunu Tenggu; Bhisa Vitus Wihelmus; Ngongo Dede (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study examines the implementation of criminal law against gambling practices in traditional horse racing involving minors in East Sumba Regency. The research employed an empirical legal method with a qualitative approach to analyze the application of criminal law and the factors influencing its enforcement. Primary data were collected through interviews with law enforcement officers, race organizers, gamblers, and children involved in horse racing activities, while secondary data were obtained from legislation, legal literature, and relevant documents. The findings indicate that criminal law enforcement has been carried out through both repressive and preventive measures, including law enforcement operations, legal awareness campaigns, and rehabilitation efforts involving the Correctional Center (BAPAS). However, its effectiveness remains limited due to strong cultural acceptance of gambling, inadequate law enforcement personnel, extensive supervision areas, low public legal awareness, and permissive social environments. The study further reveals that the involvement of customary leaders and local communities is essential to balancing cultural preservation with legal compliance and child protection. Therefore, strengthening inter-institutional collaboration, preventive legal education, and community participation is necessary to improve the effectiveness of criminal law enforcement while safeguarding children's rights in traditional horse racing events.